Improving the Teaching of ICT Engineering using Flipped Learning: a personalized model and a case study - Abdelhak Aqqal; Asmaa Elhannani; Abdelfatteh Haidine; Aziz Dahbi (Production)
Abstract In recent years, Flipped Classroom started to be used as an effective way of teaching Engineering among various strategies in higher education. However, enabling and using the flipped learning is a complicated task, not a straightforward goal that can be simply achieved through a combination of face-to-face and online activities. It requires a more sophisticated understanding of effective teaching methods to manage the shift from the traditional to the flipped learning and the optimum adaptation of technology as part of this change. Given this challenge, this research work provides a personalized model of the flipped classroom and investigates through a case study in an Engineering School how our approach can be used to improve teaching of Information and Communication Technology (ICT) Engineering. It assesses by using empirically data related to the interaction of the various actors at different levels of abstraction, particularly from a gender perspective, the relevance and the impact of the flipped classroom on student learning and achievement in ICT Engineering Education.